Kajian Hubungan Allometrik dan Biomassa Lamun Thalassia hemprichii sebagai Bioindikator Lingkungan - Andi Zulfikar; Mennofatria Boer; Luky Adrianto; Reny Puspasari (Institut Pertanian Bogor, 2020)
Seagrass has long been known to be very sensitive to environmental changes, especially caused by human activities (anthropogenic disturbance) and has been used as a bioindicator for environmental condition. This research aimed to study interaction of Thalassia hemprichii measured and derived variables (metrics), at two locations i.e., inhabited island (high anthropogenic location) and uninhabited island (low anthropogenic location). Confirmative approach was conducted using a developed conceptual model based on preliminary studies, the conceptual model was analyzed in multivariate context using data from field observation. The result showed that Thalassia hemprichii dominated and have higher above ground biomass value in inhabited area which indicated high nutrient input, meanwhile uninhabited area showed a higher below ground biomass value. Above ground of Thalassia hemprichii that have direct effect on its biomass and below ground metrics was leaf width, meanwhile leaf length of Thalassia hemprichii have indirect effect on its biomass and below ground metrics. The result also indicated some different metric covariations which were influenced by the degree of Thalassia hemprichii density. Leaf length, leaf width, density, and percent cover of Thalassia hemprichii potentially could be used as components in multimetric index and bioindicator for environmental quality. Keywords: anthropogenic disturbance, path analysis, structural equation modeling, Thalassia hemprichii